(untitled) (Research, Society and Development, 2025)
This research aimed to report the clinical, laboratory, electrocardiography, and image findings from an 8-year-old male Rottweiler with ventricular preexcitation. A qualitative, descriptive investigation of the specific type of clinical case report in the veterinary field was carried out. Blood tests revealed renal insufficiency, classified as chronic kidney disease (CKD), IRIS stage-3. The electrocardiography demonstrated sinus rhythm and intermittent ventricular preexcitation. Echocardiographic findings were within the normal reference range. The thoracic radiographs indicated pulmonary nodules and significant pleural effusion. A few days after cardiology evaluation, the patient died, raising clinical suspicion of pulmonary lymphoma.